2010
DOI: 10.1088/0957-4484/21/38/385702
|View full text |Cite
|
Sign up to set email alerts
|

Towards strain gauges based on a self-assembled nanoparticle monolayer—SAXS study

Abstract: An in situ small-angle x-ray scattering study of the nanoparticle displacement in a self-assembled monolayer as a function of a supporting membrane strain is presented. The average nanoparticle spacing is 6.7 nm in the unstrained state and increases in the applied force direction, following linearly the membrane strain which reaches the maximum value of 11%. The experimental results suggest a continuous mutual shift of the nanoparticles and their gradual separation with the growing stress rather than nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 17 publications
(19 reference statements)
4
42
0
1
Order By: Relevance
“…At a strain of 0.5%, a sensitivity DR=R e of 70 is reached which is comparable to that of the NP-based strain gauges elaborated from colloidal solutions. 13,14,17,19,20 As previously suggested in the literature, [13][14][15][16][17][18][19][20] the exponential increase of DR/R with tensile strain e which is observed in Fig. 3(b) is consistent with the exponential dependence of tunnelling resistance on the interparticle separation distance.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…At a strain of 0.5%, a sensitivity DR=R e of 70 is reached which is comparable to that of the NP-based strain gauges elaborated from colloidal solutions. 13,14,17,19,20 As previously suggested in the literature, [13][14][15][16][17][18][19][20] the exponential increase of DR/R with tensile strain e which is observed in Fig. 3(b) is consistent with the exponential dependence of tunnelling resistance on the interparticle separation distance.…”
supporting
confidence: 89%
“…1 For the last ten years, the research on piezoresistive transducers has mainly been focused on the use of nanomaterials to optimize sensitivity, power consumption, and sensor miniaturization. For instance, Si nanowires, [2][3][4] carbon nanotubes, [5][6][7] graphene, [8][9][10] MoS 2 , 10 SiC nanoribbons, 11 Ag nanowires, 12 and metallic nanoparticle (NP) assemblies [13][14][15][16][17][18][19][20] have been exploited at the laboratory scale to achieve very large gauge factors (GFs) which rival the state-of-the-art bulk Si gauges. Although the use of nanomaterials has attracted a lot of attention in the literature these past few years, many technological obstacles (manipulation of individual nanostructures, complexity of the process, sensor reproducibility, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Siffalovic et al 121 showed using small angle X-ray scattering that the strain in Fe 2 O 3 nanoparticle networks on mylar is spread homogeneously over the substrate. Shall the network break at one location and remains unstrained at others, an accurate strain measurement will not be possible due to the symmetry of the structure.…”
Section: High Sensitivity Quantum Strain Gaugesmentioning
confidence: 99%
“…A guess of the possible explanation is the difference between local and macroscopic strain for NPs supported by flexible substrate 21 . Recent experiments on small angle X-ray scattering for monolayer NP films revealed opposite results for various substrates and this local strain issue is under debate 23 24 . Farcau and co-workers also found that the dimensionality of NP films has a strong impact on g : the confinement of conduction paths gives NP monolayer a larger g than multilayers 15 .…”
mentioning
confidence: 99%